The Patterson syndrome, leprechaunism, and pseudoleprechaunism. - David, T J (1981)
A bizarre syndrome has hitherto masqueraded as leprechaunism, and although it is a quite different disorder it has been used as the prototype of leprechaunism in some birth defects atlases. It is proposed that this condition is designated the Patterson syndrome and details of a second case are reported. The features of this connective tissue and neuroendocrine disorder include bronzed hyperpigmentation, cutis laxa of the hands and feet, bodily disproportion, severe mental retardation, and major bony deformities. Radiographs revealed a unique and gross generalised skeletal dysplasia, unlikely to be confused with any other disorder. This endocrine abnormality comprised hyperadrenocorticism, cushingoid features, and diabetes mellitus in the first case, and premature adrenarche in the second case. The pathogenesis and aetiology of the Patterson syndrome are unknown, although quantitative and qualitative abnormalities of mucopolysaccharide excretion were found in the second case.